Restoration of riparian vegetation on a mountain river degraded by historical mining and grazing. (6th October 2021) - Cubley, Erin S.; Richer, Eric E.; Baker, Daniel W.; Lamson, Chris G.; Hardee, Travis L.; Bledsoe, Brian P.; Kulchawik, Peter L.
Abstract: Riparian ecosystems in montane areas have been degraded by mining, streamflow alterations, and livestock grazing. Restoration of ecological and economic functions, especially in high‐elevation watersheds that supply water to lower elevation urban and agriculture areas is of high priority. We investigated the response of riparian vegetation and bank stability following channel treatments and riparian habitat restoration along a segment of the upper Arkansas River south of Leadville, Colorado. The study area has been historically degraded by heavy‐metal mining and is designated a U.S. Superfund site. Additionally, trans‐basin water diversions and livestock grazing have contributed to channel widening and altered vegetation composition and cover. We used a before‐after‐control impact study design in four reaches with varied contamination and grazing history to assess restoration success. Before restoration, streambanks were dominated by graminoids and total vegetation cover varied among reaches with willow cover less than 16% in three reaches. Post‐restoration, changes in total vegetation cover fell short of projected goals, but willow cover was greater than 20% in all study reaches. The increase in woody cover likely contributed to reduced erosion and vegetation encroachment post‐restoration. Differences in functional group cover among reaches persisted post‐restoration and may be attributed to soil contamination levels and low willow seed rain and dispersal. These results highlight the importance of setting realistic restoration goals based on elevation and past land use. We recommend further remediation of fluvial tailings with low vegetation cover and continued monitoring of willow height and cover to determine if further restoration activities are needed.